Immune cell membrane-based biomimetic nanomedicine for treating cancer metastasis - Lingling Zhu; Xianzhe Yu; Ting Cao; Hanyu Deng; Xiaojun Tang; Qing Lin; Qinghua Zhou (Elsevier, 2023)
Metastasis is the leading cause of cancer-related death. Despite extensive treatment, the prognosis for patients with metastatic cancer remains poor. In addition to conventional surgical resection, radiotherapy, immunotherapy, chemotherapy, and targeted therapy, various nanobiomaterials have attracted attention for their enhanced antitumor performance and low off-target effects. However, nanomedicines exhibit certain limitations in clinical applications, such as rapid clearance from the body, low biological stability, and poor targeting ability. Biomimetic methods utilize the natural biomembrane to mimic or hybridize nanoparticles and circumvent some of these limitations. Considering the involvement of immune cells in the tumor microenvironment of the metastatic cascade, biomimetic methods using immune cell membranes have been proposed with unique tumor-homing ability and high biocompatibility. In this review, we explore the impact of immune cells on various processes of tumor metastasis. Furthermore, we summarize the synthesis and applications of immune cell membrane-based nanocarriers increasing therapeutic efficacy against cancer metastases via immune evasion, prolonged circulation, enhanced tumor accumulation, and immunosuppression of the tumor microenvironment. Moreover, we describe the prospects and existing challenges in clinical translation.